THE SYSTEM OF COMPLEX GOVERNING SOLID WASTE MANAGEMENT IN THE CONTEXT OF SUSTAINABLE REGIONAL DEVELOPMENT - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Rudenko, O. M. (Scientific Progress & Innovations, 2020)
The problem of solid waste management is one of the most important environmental, economic, and social problems of the regional development. Yearly, about 480 thousand tons (1.6 million m3) of solid domestic waste products are generated in Poltava region, and they are disposed in 377 authorized solid domestic waste landfills and dumps; also 4.5 million tons of industrial wastes are formed (200 thousand tons of which are dangerous waste products). The tendency is observed as to yearly increasing the formation of both industrial, including dangerous and domestic wastes. Moreover, the questions directed at obtaining desirable effect of using the potential in the area of waste management as a part of gross economic potential of the regional economy taking into account environmental factors and as a result of mutual activity of the participants in the area of solid waste management, have not yet received corresponding study. Taking into account all the above mentioned problems, theoretical and conceptual model of controlling the system of solid waste management at the regional level has been developed and scientifically substantiated. Based on this model, the algorithm of decision making in the area of waste management has been formulated, optimal managerial strategies in this area and mechanisms of their implementation have been determined. The developed algorithm enables to solve the questions of optimizing the development of the sphere of solid waste management having the given plurality of variables and parameters of the system’s condition for specific type of waste life cycle. The algorithm also enables to work out optimal system of waste management, having the given system parameters in the region. Target functions of governing the area of waste management, directed at optimizing economic, ecological, and social criteria of regional development have been determined. Recommendations have also been given as to improving the mechanisms of complex regional governing the sphere of solid waste management at all stages of its life cycle. Such recommendations help achieve extreme significance of target functions in governing this sphere. The obtained research results are directed at creating the basis for the development of target programs for environmental protection and also waste management in the context of the region’s synergic development.